1966
DOI: 10.1136/oem.23.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Manganism: Preliminary Observations on Glucose Tolerance and Serum Proteins

Abstract: An intravenous glucose tolerance test was carried out in i i patients with chronic manganese poisoning. Prolonged reactionary hypoglycaemia was observed. The underlying mechanism is discussed. It may be due to a disturbance of the hypothalamo-pituitary-adrenal axis.In seven of these patients total serum proteins were estimated and were separated electrophoretically. The albumin: globulin ratios were lower in patients than in controls. There were significant reductions in serum albumin concentrations and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Interest in trace elements has been steadily increasing over the last 20 years as alteration in the metabolism in several trace elements including Zinc 1 and magnesium 2,3 have been associated with impaired insulin release, insulin resistance and glucose intolerance in experimental animals and humans. The resulting chronic hyperglycaemia damages blood vessels and nerve cells producing micro vascular complications such as diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in trace elements has been steadily increasing over the last 20 years as alteration in the metabolism in several trace elements including Zinc 1 and magnesium 2,3 have been associated with impaired insulin release, insulin resistance and glucose intolerance in experimental animals and humans. The resulting chronic hyperglycaemia damages blood vessels and nerve cells producing micro vascular complications such as diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…When interpreting the previous findings, it should be noted that the most accurate circulating Mn levels are obtained from whole blood, not serum or plasma, since over 60% of blood Mn is found in erythrocytes (78). Interestingly, intravenous glucose tolerance tests in individuals with chronic manganism revealed reactionary hypoglycemia, which was proposed to be due to dysregulation of the hypothalamuspituitary-adrenal axis (79). Human genetic variants in SLC39A8 are linked to blood Mn levels as well as body mass index, total cholesterol, and HDLcholesterol (80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 97%
“…Primary studies (Baly et al, 1984; Rognstad, 1981; Tolbert et al, 1981) have indicated that in vitro gluconeogenesis is increased by Mn supplementation through its metalloenzyme and activator role in pyruvate carboxylase and mitochondrial phosphoenolpyruvate carboxykinase (PEPCK), respectively. Hence, recent studies (Baly et al, 1984; Hassanein et al, 1966) demonstrated that glucose metabolism, insulin secretion and insulin‐induced glucose uptake are limited during Mn deficiency. So, a high concentration of glucose in sheep and newborn lambs treated by maternal organic Mn in this study can be associated with Mn function in gluconeogenesis and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%